AMBIGUITAS KEWENANGAN ANTARA PEMERINTAH PUSAT DAN DAERAH PASCA UNDANG-UNDANG CIPTA KERJA - Anhar Nasution; Irwansyah Irwansyah; Muhammad Iqbal (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
The allocation of authority between the central government and local governments is a fundamental element in the decentralization system of the unitary state of the Republic of Indonesia. However, the enactment of Law Number 11 of 2020 on Job Creation (the Job Creation Law) has led to ambiguity in the distribution of power, which significantly affects the effectiveness of regional autonomy. This law restructured numerous sectoral laws, including Law No. 23/2014 on Regional Government, using an omnibus law approach that has generated both structural and substantive consequences for the governance system. This study employs a normative juridical method using statutory and conceptual approaches. The data sources consist of primary legal materials such as laws and Constitutional Court decisions, as well as secondary data from relevant scholarly journals published in the last five years. The analysis was conducted qualitatively through a critical normative review of conflicting legal norms. The findings indicate that since the enactment of the Job Creation Law, there has been a significant shift of authority from regional to central government, particularly in business licensing, spatial planning, and environmental management. Legal ambiguities arise due to inconsistencies between parent legislation and its derivative regulations, as well as the vague interpretation of legal phrases that are delegative and general in nature. As a result, legal gaps emerge between the constitutional mandate for decentralization as stipulated in Article 18 of the 1945 Constitution and the centralized practices embedded in the Job Creation Law and its implementing regulations. A reformulation of the central-local government relationship is urgently needed, adopting a more harmonious and cooperative framework that upholds the genuine principle of autonomy in accordance with the Constitution. Such efforts are essential to prevent jurisdictional conflicts, enhance the legitimacy of local governments, and ensure justice and efficiency in governance